2020
DOI: 10.1155/2020/6308289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic-Environmental Interaction on Chinese Childhood Myopia

Abstract: Objective. The purpose of this study was to evaluate the effect of genetic-environmental interaction on myopia in Chinese children aged 6 to 9 years. Methods. Students had the physical examination and were required to provide basic demographic information. Their families were asked to fill in a questionnaire concerning factors related to myopia. Multiple regression analysis was performed, and adjusted risk ratio values were calculated to assess the role between gene and environment. Value of the environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…For the cross-sectional studies, null findings were observed in 2/14 studies [ 63 , 100 ], more sedentary behaviour was unfavourable for risks/harms in 5/14 studies [ 94 , 101 – 104 ], and mixed in 7/14 studies [ 99 , 105 110 ]. More sedentary behaviour was consistently unfavourable for risks/harms when compared to recess/PE (indicating recess/PE was beneficial for preventing risks/harms) [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the cross-sectional studies, null findings were observed in 2/14 studies [ 63 , 100 ], more sedentary behaviour was unfavourable for risks/harms in 5/14 studies [ 94 , 101 – 104 ], and mixed in 7/14 studies [ 99 , 105 110 ]. More sedentary behaviour was consistently unfavourable for risks/harms when compared to recess/PE (indicating recess/PE was beneficial for preventing risks/harms) [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…More screen time was also consistently unfavourable for risks/harms [ 104 ]. More homework was consistently null in 2/12 studies [ 63 , 100 ] and unfavourable for risks/harms in 3/12 studies [ 94 , 101 , 102 ]. Mixed findings for homework included dose-response relationships in 5/12 studies, with unfavourable results (e.g., “too much” homework associated with more shoulder pain), null results (e.g., no association between “not enough” homework and shoulder pain), and favourable results (e.g., 6–8 h/day of studying or sitting associated with less neck and shoulder pain [sample median: 8–10 h/day of studying or sitting]) [ 99 , 105 – 107 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire which was developed and validated for the annual national project “Surveillance for common disease and health risk factors among students” since 2016, was used to collect lifestyle behaviors information in the present study. The validity of the questionnaire has been published previously ( 21 , 22 ). Three sets of questionnaires were used in students at primary schools, middle/high schools, and universities.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Nonmyopic children and lack of other serious eye diseases (2) Chinese Han nationality students (3) e ability of parents/guardians to provide informed consent Detailed information can be seen in previous studies [10,13].…”
Section: 2mentioning
confidence: 99%
“…Myopia is a complicated disease, and genetic as well as environmental factors contribute to its development [9]. Previously, we have demonstrated that environmental factors may play the leading role in forming myopia in Chinese children [10]. In a family, the parenting styles provided an environmental framework for children's psychosocial growth and were assumed to shape children's behavior [11].…”
Section: Introductionmentioning
confidence: 99%